(untitled) (REMUNOM, 2024)
The study addresses the interrelationship between plant nutrition and resistance to pests and diseases, highlighting the importance of adequate nutritional management in the context of sustainable agriculture. The main objective of the study was to analyze how different nutrients influence plant resistance to pests and pathogens, seeking to identify management practices that can increase the resilience of agricultural crops. Balanced nutrition significantly improves plant resistance to pests and diseases. Plants with nutrient deficiencies were more susceptible to infections and insect attacks, while those with adequate nutrition were more capable of producing defensive compounds and maintaining cellular integrity. Plant nutrition, when well adjusted, not only improves productivity, but also strengthens the natural defense of plants, reducing the need for chemical interventions. The study suggests that the integration of adequate nutritional practices in agricultural management can significantly contribute to the sustainability and resilience of crops in the face of biotic challenges.